Assessment and perspective of Vietnamese consumers’ pork handling and eating practices - Sinh Dang Xuan; Phuc Pham Duc; Unger, Fred; Makita, K.; Ngan Tran Thi; Hung Pham Van; Grace, Delia; Hung Nguyen-Viet (Hanoi School of Public Health, 2016)
Objectives: We investigated how the consumers’ practices of eating and handling pork are related to food safety in Hung Yen and Nghe An provinces, Vietnam. Methods: A cross-sectional survey with interview of 416 respondents and six focus group discussions were conducted. Information on household diet, pork selection and purchase, processing, consumption and knowledge regarding pig originated food were analyzed. Results: On average, consumers purchased 0.68 (0.2-2) kg of pork/time for 4 to 5 household members. The pork was purchased in the morning (7.45; 4.30-11.30 am) and almost exclusively originated from open market (99%). The pork was kept for 1.5 (0-24) hours at room temperature (54.6%) or in the fridge (45.4%). To prepare raw and cooked pork using the same knife (80.9%) and/or cutting board (75.1%) was recorded. With an average 4 pork meals/week, the amount of pork consumed per household member was 81 grams/meal. The knowledge of respondent on pork safety was higher in Hung Yen than in Nghe An. Conclusions: Findings are crucial for health risk exposure assessment related to pork/pork products and more effective risk communication programs targeting Vietnamese pork consumers.